Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Komitmen Pegawai (Studi Pada Universitas Sjakhyakirti Palembang) - Indah Mawarni; Tutik Pebrianti; Imam Suroso; Aras Tulip (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
This research isconducted to find outthe influence of leadership style and organizational culture partially and simultaneously employees commitment at Sjakhyakirti University of Palembang. Data areobtained from questionnaires. The respondents areall staffs and lecturers at Sjakhyakirti University of Palembang. The results of the research analyzeusing Multiple Linear Regression which Leadership styles and organizational culture havea significant influence to employees commitment also leadership style and organizational culture simultaneously have a significant effect on employees commitment. It is suggested that the leadership of Sjakhyakirti University of Palembangmaintainsa participative and delegative stylesin orderto maintainthe affective commitment of the employees in University of Sjakhyakirti. The leader should pay attention to discipline and employees developmentbecauseit will certainly impact on the sustainability commitment of employees and lecturers in Sjakhyakirti University of Palembang.